2021
DOI: 10.1101/2021.05.17.444501
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plastic mulches reduce adult and larval populations ofDrosophila suzukiiin fall-bearing raspberry

Abstract: The invasive spotted-wing drosophila, Drosophila suzukii, is a major pest of fruit crops world-wide. Management of D. suzukii relies heavily on chemical control in both organic and conventional systems, and there is a need to develop more sustainable management practices. We evaluated the efficacy of three colors of plastic mulches at reducing populations of D. suzukii in fall-bearing raspberry and assessed the mulches' impacts on canopy microclimate factors relevant to D. suzukii. Black, white, and metallic p… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 64 publications
(104 reference statements)
0
9
0
1
Order By: Relevance
“…Covering the ground with UV-reflective material may disrupt orientation and flight (Shimoda & Honda, 2013). Radiance measurements taken concurrently with this study in the same research plots found that the mulches increased canopy radiance in the UV spectrum (McIntosh et al, 2021(McIntosh et al, , 2023. This may explain why the metallic mulch decreased the abundance of Coleoptera, micro-Hymenoptera, Opiliones, Orthoptera, and Thysanoptera, why the white mulch decreased Opiliones and Orthoptera, and the black decreased Orthoptera and Thysanoptera in all weeks of the study compared to the control (Croxton & Stansly, 2014;Frank & Liburd, 2005;McIntosh et al, 2021McIntosh et al, , 2023Nottingham & Beers, 2020;Nottingham & Kuhar, 2016;Rhainds et al, 2001;Summers et al, 2010).…”
Section: Discussionmentioning
confidence: 62%
See 4 more Smart Citations
“…Covering the ground with UV-reflective material may disrupt orientation and flight (Shimoda & Honda, 2013). Radiance measurements taken concurrently with this study in the same research plots found that the mulches increased canopy radiance in the UV spectrum (McIntosh et al, 2021(McIntosh et al, , 2023. This may explain why the metallic mulch decreased the abundance of Coleoptera, micro-Hymenoptera, Opiliones, Orthoptera, and Thysanoptera, why the white mulch decreased Opiliones and Orthoptera, and the black decreased Orthoptera and Thysanoptera in all weeks of the study compared to the control (Croxton & Stansly, 2014;Frank & Liburd, 2005;McIntosh et al, 2021McIntosh et al, , 2023Nottingham & Beers, 2020;Nottingham & Kuhar, 2016;Rhainds et al, 2001;Summers et al, 2010).…”
Section: Discussionmentioning
confidence: 62%
“…Different colours of plastic mulches can reduce specific pests in fruit and vegetable crops, including aphids (Ban et al, 2009;Farias-Larios & Orozco-Santos, 1997;Greer & Dole, 2003), whiteflies (Simmons et al, 2010), Asian citrus psyllid (Croxton & Stansly, 2014), tarnished plant bug (Lygus lineolaris (Palisot de Beauvois); Rhainds et al, 2001), Mexican bean beetle (Epilachna varivestis Mulsant; Nottingham & Kuhar, 2016), and pear psylla (Cacopsylla pyri (L.); Nottingham & Beers, 2020). Recently, we showed that plastic mulches can effectively control spotted-wing drosophila (Drosophila suzukii Matsumura) in raspberries (McIntosh et al, 2021(McIntosh et al, , 2023. Few studies have directly tested the mechanisms by which the plastic mulches control insect pests, though it is likely related to microclimate modifications like increased reflection of light into the plant canopy or unfavourable changes in canopy humidity or temperature (McIntosh et al, 2021(McIntosh et al, , 2023Nottingham & Beers, 2020;Nottingham & Kuhar, 2016).…”
mentioning
confidence: 99%
See 3 more Smart Citations